Sustainable Political Leadership Based on System Thinking in Rural Development Practices of Nepal - Sharma, Rishi Ram (Research Nepal Journal of Development Studies, 2021)
The sustainable political leadership based on system thinking is a highly qualified skillful political leadership on sustainable development administration on rural development practices of Nepal. This paper analyses the quality of sustainable political leadership based on system thinking in overall sustainable rural development application and process in Nepal and its empiricisms. It also presents the national and international context of leadership, system thinking and sustainable development and their contemporary debates and issues. Methodologically it is an empirical literature review on sustainable development, system thinking and leadership for Rural Development and its practices in Nepal. In conclusion, in Nepal social inclusion, justice, and equity; economic and ecological balance and good governance in a basket of rural development is essential phenomena for sustainable political leadership based on system thinking. The real practices of the ideas of social inclusion, justice, equity; economic and ecological balance and good governance to increase productivity of sustainable political leadership is to be more important. However, these types of practices on sustainable political leadership based on system thinking are insignificant, qualities and practices both are low. The national and international importance and urgency of sustainable political leadership based on system thinking are increasing to maintain sustainability governance from local to global level.